CONSIDERATIONS ON THE CELLULOSE AND PAPER INDUSTRY IN ROMANIA (PANGEEA, 2025)
In the following lines, we will find a past and present radiography of the cellulose and paper industry in Romania. Data on cellulose and paper industry, aspects from the history and the present of the production units will be provided.
Keywords: industry; cellulose; paper